Cardioproteção induzida por p-cimeno contra danos contráteis e oxidativos decorrentes das lesões de reperfusão em ratos - Sá, Lucas Andrade de (2017)
Acute myocardial infarction (AMI), a serious public health problem, is characterized by tissue death after prolonged ischemia. Ischemia, the repercussion, triggers cellular processes, such as intracellular calcium overload and oxidative stress. There are few pharmacological intervention strategies for prevention and limitation of these lesions, and it is worth noting that the available forms of intervention are not fully effective. Recent research indicates that, as a therapeutic alternative, the use of drugs derived from natural products with antioxidant action has been shown to be an important preventive and treatment tool for the lesions resulting from the infarction. p-Cymene, a monoterpene present in essential oils of various plant species, is a substance that has a range of proven pharmacological activities, among them antinoceptive, anti-inflammatory and antioxidant activity. The aim of this study was to evaluate the effect of pre-treatment with p-cymene on ischemia and reperfusion injury (I / R) in hearts isolated from rats. For this purpose, the Langendorff-type aortic perfusion model was used to submit isolated hearts from rats to global ischemia. Wistar rats pretreated with vehicle or p-cymene at the dose of 150 mg / kg / day orally (gavage) were used for 7 days, and thereafter their isolated hearts were subjected to global ischemia and reperfusion in the Langendorff system . As a control of the adopted experimental model, hearts that were not submitted to I / R were used. Measurements of lactate dehydrogenase (LDH), indicative of tissue damage, were also performed on all groups of animals, and the contractile parameters in the isolated heart (left ventricular pressure (LVDP), time derivative of ventricular pressure (dP / Dt) and arrhythmia severity index (ASI)], as well as oxidative parameters in cardiac tissue [malonaldehyde formation (MDA), total sulfhydryl; The activity of the antioxidant enzymes catalase (CAT), superoxide dismutase (SOD), glutathione reductase (GR) and glutathione peroxidase (GPx)]. We observed that the pre-treatment with p-cymene preserved the reduction of PDVE, dP / dt and caused lower ASI, improving the contractile function. It reduced the formation of MDA and LDH (62%). In addition, this monoterpene preserves the sulfhydryl groups (38%) and the activity of the antioxidant enzymes CAT (36%), SOD (62%), GPx and GR when compared to the vehicle. It can be concluded that pre-treatment with p-cymene prevents the reduction of cardiac contractile force caused by ischemia and significantly reduces the oxidative damage caused by infarction in the experimental model.